The Development of Information Management Process for Nursing Quality Indicators for Nursing Organization at Nonghin Hospital, Loei Province - Mulkruakum, Ruttikorn (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Information management for nursing quality indicators is essential for healthcare administration and quality improvement. However, many community hospitals face challenges in systematic data collection, analysis, and reporting processes, directly affecting administrative decision-making and patient safety. The objective to develop an information management process for nursing quality indicators and evaluate its outcomes at Nonghin Hospital Nursing Organization, Loei Province. This research and development study was conducted from October 2024 to May 2025, involving 28 nursing staff members selected by purposive sampling. The study employed the PDCA (Plan-Do-Check-Act) cycle and AIC (Awareness-Interest-Commitment) process. Research instruments included: (1) practice activity questionnaire (KR-20 reliability = 0.72), (2) quality assessment form (KR-20 reliability = 0.78), and (3) information management manual covering 9 nursing quality indicators. Data were analyzed using descriptive statistics and Wilcoxon signed-rank test. The developed information management process consisted of five steps: data acquisition, data collection, data storage, data processing, and data dissemination. After six months of implementation, the quality of information management significantly improved from moderate level (mean = 11.2, SD = 2.6) to high level (mean = 19.4, SD = 1.2) (Z = −4.63, p < 0.001). Staff practice scores also increased significantly from moderate (mean = 10.8, SD = 2.4) to high level (mean = 18.6, SD = 1.8) (Z = −4.62, p < 0.001). The developed information management process using the PDCA cycle with AIC process effectively improved nursing quality indicator management, resulting in reliable data for administrative decision-making and quality enhancement.